SEMIDIURNAL VARIATIONS IN DILUTION OF SEA WATER AT COCHIN HARBOUR - A TROPICAL ESTUARINE HARBOUR - J, Sundaresan (Indian Journal of Fisheries, 2011)
The changes in freshwater fraction at the surface, middle and botom waters of Codiin harbour area arestudied during springtide and neaptide. [hiring springtide the surface waters of the inner channelsexhibits gradual dianges in freshwater fraction relative to cut. Mid water freshwater fraction changes aremore in symmetry with the tide and the changes are maximum at Emakulam channel (46.29 - 29.4%) inspringtide. The incursion of coastal saline water was observed to be prominent at the mid water levelsduring neaptide. Low freshwater fraction is present at bottom water of all the stations during neaptide.